1991
DOI: 10.1530/acta.0.1250280
|View full text |Cite
|
Sign up to set email alerts
|

Follicle-stimulating hormone-dependent estrogen secretion by rat Sertoli cells in vitro: Modulation by calcium

Abstract: We have investigated the role of Ca2+ in the control of FSH-induced estradiol secretion by Sertoli cells isolated from 8-10 days old rats. Exogenous Ca2+ (4-8 mmol/1) inhibited FSH-stimulated E2 secretion such that, with 8 mmol/l Ca2+ and FSH (8 IU/l) E2 secretion decreased from 2091\m=+-\322to 1480\m=+-\84 pmol/l (p<0.002), whilst chelation of Ca2+ in the culture medium with EGTA (3 mmol/l) increased E2 secretion from 360\m=+-\45to 1242\m=+-\133pmol/l) in the absence of FSH. Further, EGTA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…In addition, these results show that ATP effects are produced at a site distal to cAMP production. Our results agree with previous observations demonstrating that PKC activity and intracellular Ca 2+ levels are involved in the regulation of aromatase activity at a site distal to cAMP accumulation (Monaco & Conti 1987, Talbot et al 1991. ATP regulation of other steroid-producing cells, like granulosa and Leydig cells, has recently been presented (Kamada et al 1994, Foresta et al 1996.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, these results show that ATP effects are produced at a site distal to cAMP production. Our results agree with previous observations demonstrating that PKC activity and intracellular Ca 2+ levels are involved in the regulation of aromatase activity at a site distal to cAMP accumulation (Monaco & Conti 1987, Talbot et al 1991. ATP regulation of other steroid-producing cells, like granulosa and Leydig cells, has recently been presented (Kamada et al 1994, Foresta et al 1996.…”
Section: Discussionsupporting
confidence: 92%
“…The physiological significance of the calcium regulation of Sertoli cell PG metabolism remains to be elucidated. Experiments using EGTA, verapamil, or calcium ionophore [Malléa et al, 1987;Grasso and Reichert, 1989;Talbot et al, 1991] clearly indicate that calcium antagonizes the stimulatory effect of FSH on cAMP production and aromatase activity in Sertoli cells by an unknown mechanism. In addition, we have previously demonstrated that cellular HSPG level is inversely correlated with FSH-stimulated estradiol production [Phamanthu et al, 1995[Phamanthu et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments using EGTA, verapamil, or calcium ionophore [Malléa et al, 1987;Grasso and Reichert, 1989;Talbot et al, 1991] clearly indicate that calcium antagonizes the stimulatory effect of FSH on cAMP production and aromatase activity in Sertoli cells by an unknown mechanism. In addition, we have previously demonstrated that cellular HSPG level is inversely correlated with FSH-stimulated estradiol production [Phamanthu et al, 1995[Phamanthu et al, , 1999.…”
mentioning
confidence: 99%